The Duty to Breastfeed. Mothering, Wet-Nursing and Abandoned Childhood in Ancient Regime Lombardy: First Historical-Legal Researches (Italian Review of Legal History, 2024)
The history of mothering and wet nursing is a topic of enormous importance, extremely broad and characterized by multiple perspectives. Over the past decades, numerous historical, demographic, sociological, and anthropological investigations have developed on this subject. The historical-legal aspect, so far less studied, nonetheless encompasses a series of profiles of great interest for better understanding the role of women within society and their ability to influence or not the legal aspects related to their status as mothers, the care, and education of children.In a historical period, such as the modern era, when newborns could not be artificially fed, wet nursing represented their only chance of survival, both within upper-class families, where the practice of sending children to wet nurses was very ancient, and in the equally dramatic and widespread case of child abandonment.The following pages will first frame the phenomenon of wet nursing through the centuries, tracing, starting from ancient times, the main voices of a vast medico-philosophical literature favorable to maternal breastfeeding and, conversely, critical and distrustful of the practice of entrusting the child to a wet nurse. From Quintilian to Soranus of Ephesus, from Pseudo-Plutarch to Aulus Gellius, all agreed on the importance of maternal care, starting with breastfeeding, for the establishment of a strong emotional bond between mother and child. In cases where it was necessary to resort to a wet nurse, the choice had to be made with great care, as a good wet nurse had to present precise physical and moral qualities.These requirements remained unchanged in the treatises of medieval and modern times until, between the seventeenth and eighteenth centuries, a new way of understanding relationships within the family began to develop in the thought of the intellectuals of the time, with significant repercussions also in the field of breastfeeding. For the first time, the criteria adopted for centuries in the search for a wet nurse were questioned by a series of scientific studies conducted on the causes of infant mortality, which considered maternal milk a resource against diseases and deaths in the first years of life.J.-J. Rousseau, in his famous pedagogical novel Émile, ou de l’éducation (1762), was a fervent supporter of maternal breastfeeding as the first and fundamental act intended to consolidate the bond between mother and child, a relationship in which the duties –according to the Genevan philosopher – were reciprocal.Despite this, wet nursing was deeply rooted in the ancien régime society. In the case of an aristocratic or mercantile family, the wife was destined to procreate as many children as possible – in a historical period when infant mortality was extremely high – hence,not breastfeeding the newborn was the preferable choice so that the woman would become fertile again shortly after childbirth. Breastfeeding was also considered a source of fatigue for the woman already exhausted by labor and delivery, and it was believedthat breastfeeding had a negative effect on the woman’s beauty, causing her to wither prematurely. Moreover, breastfeeding represented an obstacle to the resumption of sexual relations between husband and wife, which was thought to spoil the mother’s milk.For all these reasons, in the middle and upper-class families, immediately after the birth of a child, it was necessary to find a wet nurse to whom the baby could be entrusted. But even more in the case of abandoned children, finding a wet nurse willing to provideher milk was crucial for the survival of the numerous abandoned babies.In Milan, the practice of assisting foundlings and pregnant women in difficulty has deep roots in the early Middle Ages, based on a charitable tradition deeply rooted in the territory, where a dense network of welfare institutions was enriched over the centuriesthanks to private beneficence and represented for a long time a typical feature of the city’s identity.As early as 1456, the Ospedale Maggiore of Milan invested significant capital in the field of abandoned childhood, arranging for the presence of internal wet nurses, milk mothers tasked with breastfeeding and caring for abandoned children until they were found a place with external wet nurses who would care for them at least until weaning.The phenomenon of child abandonment, which expanded significantly at the end of the fifteenth century, soon made the number of internal wet nurses insufficient and pushed the Ospedale Maggiore to recruit external wet nurses, usually residing in the countryside,to whom a salary was paid.Despite the careful management of the Ospedale Maggiore, the numerical imbalance between wet nurses and infants increased in the following centuries, prompting the Hospital Chapter to increase the wet nurses’ salaries and periodically offer them extramonetary rewards. The enlightened absolutism of the Habsburgs also made its effects felt in the field of abandoned children and wet nursing: during the reign of Maria Theresa, Prince Kaunitzestablished a new, more comfortable headquarters for pregnant women, abandoned children, and the wet nurses of the Ospedale Maggiore, which in 1780 were moved fromthe cramped “Quarto delle balie” to the former monastery of Santa Caterina alla Ruota, suitably renovated to house the “family of the foundlings”. With the advent of Joseph II, the system of assistance to pregnant women and the abandoned children was radicallyreformed in accordance with his intent to rationalize the management of charity. In Milan, Joseph II dissolved the Hospital Chapter, appointed a royal administrator and a medical director. The foundling wheel, where children were abandoned, was closed, and the delivery of newborns became possible, even anonymously, only through anacceptance office where the parent had to present a “certificate of poverty” or pay an advance on the child’s maintenance expenses.According to the new regulation, only pregnant women presenting the “certificate of poverty” signed by their parish priest, whether from the city or other areas of the Duchy, would be admitted free of charge to Santa Caterina alla Ruota. Should they decide toabandon their child after birth, the mothers would remain in the hospice as internal wet nurses. Only women with the certificate of poverty would not pay the foundling’s tax, thecontribution to be paid to the Santa Caterina hospice in case of abandoning an infant. In 1791, Leopold II reopened the foundling wheel, restoring the old rules for the admissionof pregnant women and the foundlings. At the request of the Ambrosian Church, the Hospital Chapter was reconstituted, and the centralized dirigisme of the Josephine period was decidedly toned down. Free wet nursing was extended to all poor newborns,children of deceased women, “unable to breastfeed” or admitted to the Hospital without any longer requiring a guarantee for their retrieval. Santa Caterina alla Ruota thus transformed into a sort of “public establishment of free wet nursing”.
Keywords: Wet-nurse; Mothering; abandoned Childhood; Ospedale Maggiore; Milan